Multi-isotope approach allows tracking the circulation of ceramics across the Andes (Argentina and Chile) - Frigolé, Cecilia Andrea (2024)
The circulation of material culture across space is a central topic in Andean archaeology and has witnessed significant growth during the last decades. Ceramics have been a part of this trend through the analysis of the abundance of chemical elements. Aiming at expanding ceramic sourcing and the study of large-scale conveyance of artefacts, we present the first multi-isotopic approach combining strontium, neodymium, and lead isotopes in South America. We explore the utility of an isoscape of bioavailable strontium for the interpretation of ceramic provenance. These first results show that this approach confidently discriminates large areas of provenance. Broadly, the sherds from styles assigned to the western Andean slope (Llolleo, El Molle, local Inka) show low strontium and lead isotope ratios with high neodymium, consistent with the young ages of underlying rocks, including samples recovered across the Andes and confirming their large-scale conveyance. Conversely, sherds assigned to eastern styles (Agrelo) display high strontium and lead ratios and low neodymium ratios. By exploring the potential of this approach to track ceramic production and conveyance, this research contributes to archaeological debates in the Andes and beyond.